The common interests of health protection and the economy: evidence from scenario calculations of COVID-19 containment policies - Florian Dorn; Sahamoddin Khailaie; Marc Stoeckli; Sebastian C. Binder; Tanmay Mitra; Berit Lange; Stefan Lautenbacher; Andreas Peichl; Patrizio Vanella; Timo Wollmershäuser; Clemens Fuest; Michael Meyer-Hermann (The European Journal of Health Economics, 2022)
We develop a novel approach integrating epidemiological and economic models that allows data-based simulations during a pandemic. We examine the economically optimal opening strategy that can be reconciled with the containment of a pandemic. The empirical evidence is based on data from Germany during the SARS-CoV-2 pandemic. Our empirical findings reject the view that there is necessarily a conflict between health protection and economic interests and suggest a non-linear U-shape relationship: it is in the interest of public health and the economy to balance non-pharmaceutical interventions in a manner that further reduces the incidence of infections. Our simulations suggest that a prudent strategy that leads to a reproduction number of around 0.75 is economically optimal. Too restrictive policies cause massive economic costs. Conversely, policies that are too loose lead to higher death tolls and higher economic costs in the long run. We suggest this finding as a guide for policy-makers in balancing interests of public health and the economy during a pandemic.
Keywords: 610; COVID-19; Optimal strategy; Economy; Deaths; Integrated simulations; Real-time analysis